HUMAN RIGHTS, THE CYPRUS PROBLEM AND THE IMMOVABLE PROPERTY COMMISSION. Issue 3 (23rd April 2018) - Erdem, Meliz; Greer, Steven
Abstract: This article critically examines the role of the Immovable Property Commission, established in 2005 by the 'Turkish Republic of Northern Cyprus' under pressure from the European Court of Human Rights, to redress losses sustained by Greek Cypriots who fled south when the island was partitioned in the mid-1970s. While the Commission has been a modest success, proceedings have been lengthy, its decisions lack transparency, there have been difficulties with restitution and exchange, and the payment of compensation has often been delayed. Corporate ownership and encumbrances, such as mortgages, have also proved problematic. But, whether it contributes negatively or positively to full resolution of the Cyprus problem, or makes no contribution at all, remains to be seen.